Tannins in the Treatment of Diabetic Neuropathic Pain: Research Progress and Future Challenges - Omar, Norsuhana; Ismail, Che Aishah Nazariah; Long, Idris (Frontiers in Pharmacology, 2022)
Diabetes mellitus and its consequences continue to put a significant demand on medical resources across the world. Diabetic neuropathic pain (DNP) is a frequent diabetes mellitus chronic microvascular outcome. Allodynia, hyperalgesia, and aberrant or lack of nerve fibre sensation are all symptoms of DNP. These clinical characteristics will lead to worse quality of life, sleep disruption, depression, and increased mortality. Although the availability of numerous medications that alleviate the symptoms of DNP, the lack of long-term efficacy and unfavourable side effects highlight the urgent need for novel treatment strategies. This review paper systematically analysed the preclinical research on the treatment of DNP using plant phytochemicals that contain only tannins. A total of 10 original articles involved in in-vivo and in-vitro experiments addressing the promising benefits of phytochemical tannins on DNP were examined between 2008 and 2021. The information given implies that these phytochemicals may have relevant pharmacological effects on DNP symptoms through their antihyperalgesic, anti-inflammatory, and antioxidant properties; however, because of the limited sample size and limitations of the studies conducted so far, we were unable to make definitive conclusions. Before tannins may be employed as therapeutic agents for DNP, more study is needed to establish the specific molecular mechanism for all of these activities along the pain pathway and examine the side effects of tannins in the treatment of DNP.